PARTISIPASI PEREMPUAN DALAM PENGELOLAAN SAMPAH YANG BERNILAI EKONOMI DAN BERBASIS KEARIFAN LOKAL - E Yuningtyas Setyawati; R Sapto Hadi Priyo Siswanto (Universitas Negeri Gorontalo, 2020)
The purpose of this study is to determine women's participation in waste management that has economic value and based on local wisdom, but also to find out the factors that cause women to process and use waste. This research is important to do because there is still a lack of environmental management by utilizing waste of economic value This study was conducted using a qualitative approach, in the form of embedded case studies. The focus of the study is the process and prospects for women's empowerment in Sitimulyo Village, Piyungan District, Bantul Regency, DIY. Data were collected by interview method and analyzed using interactive analysis methods The results showed that the form of women's participation in environmental improvement took the form of donating voluntary labor and participating in waste management. Factors that cause mothers to process waste to create a cleaner environment and increase the family economy. Organic waste management is composted, while for inorganic waste various forms of handicraft and various household equipment are made. Waste management activities are carried out by utilizing local potential, the waste management that is carried out can familiarize the mothers and economically can improve the welfare of the family.